Functional Analysis and Proteomics Profiling of Extracellular Vesicles From Swine Plasma Infected by African Swine Fever Virus - Xu, Guowei; Shi, Xijuan; Liu, Huanan; Shen, Chaochao; Yang, Bo; Zhang, Ting; Chen, Xuehui; Zhao, Dengshuai; Yang, Jinke; Hao, Yu; Cui, Huimei; Yuan, Xingguo; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
African swine fever (ASF) has brought excellent barriers to swine production in China and the world. Studies have shown that extracellular vesicles mediate the RNA and protein spread of pathogenic microorganisms and RNA and proteins. After infection by pathogenic microorganisms causes significant differences in the proteins contained within extracellular vesicles. Based on the above studies, the extracellular vesicles were extracted from ASF virus (ASFV)-infected swine plasma. And qPCR, western blot, and confocal experiment were carried out. The research shows that extracted extracellular vesicles significantly promote the replication of ASFV in susceptible and non-susceptible cells Proteomics analysis of the extracellular vesicle proteins revealed that ASFV infection could cause significant differences in the protein profile. This study demonstrates that extracellular vesicles play a critical role in ASFV replication and transmission and cause significant differences in the protein profile encapsulated in extracellular vesicles.